The greater pretender: a psychobiography of Freddie Mercury - Louw, Dewald (University of the Free State, 2017)
This study entails a psychobiography of the entertainer, Freddie Mercury (1946 – 1991). Mercury was known for his theatrical stage persona and fearless expression of his sexuality. As many other performers, Mercury became the great pretender in front of audiences, compensating his own inner desires for the satisfaction of his music fans. The workings of the mind of this musical genius with his multi-layered personality continue to intrigue music fanatics around the world. The primary aim of this study was to explore and describe the psychosocial development of Mercury within Erikson’s conceptualisation. By using a single-case psychobiographical research design, Erikson’s theory was employed to uncover and reconstruct Mercury’s life. Mercury was selected as the subject for this study by means of a non-probability purposive sampling procedure. He was undoubtedly one of the most successful music legends in entertainment history and was selected as the subject based on the interest value and unique background during his early years. 24 November 2016 marked the 25th anniversary of Mercury’s death, and numerous biographers and music historians have captured and celebrated Freddie Mercury’s life. However, Mercury’s personality development has not been analysed or documented before. In addition, a psychobiographical approach has not been employed with regard to Mercury. Various available published writings about Mercury as a world-renowned celebrity exist in the public domain. To assist in uncovering Mercury’s life history, the biographical data were collected systematically, analysed and interpreted for this psychobiography. Six distinguishable historical life periods were identified, and prominent themes in the biographical data were identified and extracted for further analysis by using Alexander’s model. Furthermore, a conceptual matrix that presented the guided analysis and discussion of the findings was compiled. The secondary aim of this study was to test the proposed psychosocial personality development theory and its principles, as stated by Erikson by means of analytical generalisation. The findings of this study suggest that Mercury to a large extent navigated through the second, third and seventh psychosocial stages successfully, while he did not resolve the crises confronted with in Erikson’s first, fourth, fifth and sixth stages. In addition, the unsuccessful resolution of earlier crises affected further development negatively, as proposed by Erikson’s theory. The study also supports the applicability and relevance of the psychosocial personality development theory for providing a systematic psychological understanding of Mercury according to Erikson’s psychosocial personality developmental theory, within a psychobiographical study.
Dissertation (M.A. (Psychology))--University of the Free State, 2017
Keywords: Farrokh Bulsara; Queen; Erikson; Psychosocial personality development; Psychobiography; Freddie Mercury; Singers; Rock music, 1971-1980